Evaluating the Role of Placental Leucine Aminopeptidase (P-LAP) in Miscarriage - Taghreed H. AL Sadoon; Ferah Gh. Al-Salihi; Adnan I. Al-Badran (Current Innovations in Medicine and Medical Science Vol. 2, 2022)
The goal of this study is to find out what role placental leucine aminopeptidase (P-LAP) plays in miscarriages and to rule out any direct or indirect effects of abortion by looking for this enzyme’s gene in miscarriages. Using the (Qiagen) QIAamp®RNA Tissues Mini Kit’s methodology, total RNA is extracted from a fresh placental tissue sample. By using 0.7% agrose gel, the sample may be seen. Following RNA extraction, samples of total RNA are reverse-transcribed using RT-PCR (QIAGEN One Step RT-PCR Kit). RT-PCR is used to amplify RT reaction samples (1 mL). The PCR products (10\(μ\)l) per lane are resolved by using electrophoresis on a 2.0% agrose gel. During a miscarriage, P-LAP may have a role in the slowed invasion of trophoblasts. The acquired data shows that there is an expression of P-LAP mRNAs in the placentas of women who are experiencing a normal pregnancy (28\(±\)0.45) and that there is a reduction in miscarriage. Furthermore, there is a difference between those with a single miscarriage and those with recurrent miscarriages. The mean values in single miscarriage (1st and 2nd) are (16.1% \(±\) 0.84) and (13% \(±\)0.24), respectively, while the mean values in recurrent miscarriage (1st and 2nd) are (12% \(±\)0.19) and (9% \(±\) 0.52), respectively. P-LAP expression is considerably lower (P = 0.05) in miscarriage and significantly lower in recurrent miscarriage compared to single miscarriage cases. The fact that there is less P-LAP mRNA in placentas from miscarriages could mean that p-LAP function is a key part of controlling pregnancy.